2012
DOI: 10.1111/jdv.12066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for body weight increment in psoriatic patients on infliximab: a multicentre, cross‐sectional study

Abstract: Severe weight increment is frequent on IFX treatment, mainly in men, and patients with severe psoriasis. Dietary follow-up or simultaneous use of methotrexate could limit this weight increment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 31 publications
4
21
0
1
Order By: Relevance
“…TNF‐α blockade may lead to an increase in leptinaemia 14 and a return to true baseline weight in the absence of inflammation 6 . The association between weight gain and baseline levels of biomarkers of inflammation (such as IL‐6), which has been found in some studies, 7,8,10,11 is consistent with this hypothesis.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…TNF‐α blockade may lead to an increase in leptinaemia 14 and a return to true baseline weight in the absence of inflammation 6 . The association between weight gain and baseline levels of biomarkers of inflammation (such as IL‐6), which has been found in some studies, 7,8,10,11 is consistent with this hypothesis.…”
supporting
confidence: 58%
“…Up to one‐fourth of patients may experience a 4–10‐kg weight gain, 2 and 32% of patients on etanercept and 25% on adalimumab had an increase in weight of more than 10% in a 48‐week evaluation 3 . According to one study, the percentage change in body weight associated with infliximab treatment of psoriasis is larger in patients with normal weight at baseline than in their overweight/obese counterparts, 5 but this finding has not been confirmed 1,6 . Normal weight participants in recent open prospective studies showed a greater increase in fat mass than lean mass compared with obese participants, 7 and weight changes correlated with fat mass gain in patients with psoriasis and with fat and lean mass gain in patients with psoriatic arthritis 8…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study revealed a 4·8 ± 5‐kg ( P = 0·005) weight increase in 16 patients after 3 years of follow‐up . A cross‐sectional prospective multicentre study reported a 1·6‐kg increase over a 1‐year period where 48·2% of patients experienced a weight increment . Two studies over a treatment period of 24 weeks found a weight gain of 2·5 ± 3·3 kg ( P = 0·004) in 40 patients, and a 2‐kg increase in 81 patients …”
mentioning
confidence: 99%